From Myanmar to Malaysia: Protracted Refugee Situations of Rohingya People - Aizat Khairi, Aizat; Askandar, Kamarulzaman; Ab. Wahab, Andika (International Journal of Engineering and Technology, 2018)
This paper examines the prolonged situation of Rohingya Refugee who are escaped from Myanmar to Malaysia for survival. Based on the literature, the Protracted Refugee Situations of rohingya people occurred due to the several factors in Myanmar and Malaysia. For example, the Rohingya people forced to escape from their place of origin because of the government persecution and also the discrimination by locals. The journey as refugees are not easy for Rohingya and they need to face some risk before reach to a new destination like Malaysia. Although the Rohingya refugee made to reach Malaysia to start a new life, another problems are emerged due to the host government policy which not recognize the status of them as refugees. Hence, the Rohingya refugees’ live in Malaysia possibility in limbo and this situation relates to the protracted refugee situations concept. However, the Rohingya refugee assuming the life in Malaysia is better than Myanmar and at the same time Malaysia also strives to find a durable solution in order to manage the Rohingya refugees’ problem.